(untitled) (Medical Forum Monthly, 2024)
Objective: To determine the frequency, sex, and cause of death in medico-legal autopsies conducted at Abbasi Shaheed Hospital. Study Design: Determination / analytic study. Place and Duration of Study: This study was conducted at the Abbasi Shaheed Hospital from January 2012 till December 2017. Materials and Methods: A 6 years case study involving the medico-legal deaths autopsied at Abbasi Shaheed Hospital. Bodies were first examined externally and then internally by dissection of body cavities. The results were collected on a structured proforma from the respective institution and were statistically analyzed using SPSS version 15. Results: Out of a total of 5131 autopsies conducted during the period of study in Abbasi Shaheed Hospital, firearm injuries were the most common cause of death followed by road traffic accident, asphyxia, assault, burn, police encounter, explosion, poisoning, fall, electrocution and others. Majority of victims being male with male to female ratio of 10:1. Conclusion: Frequency in relation to cause of death & autopsied revealed firearms injury accounting for 58.83% deaths followed by road traffic accident at 19.78%, asphyxia at 4.78% and assault at 3.73%.